Relasi islamophobia dan media massa dalam pembentukan sikap masyarakat terhadap islam di Indonesia - Hamluddin (The Journal of Religion and Communication Studies, 2024)
Islamophobia is an important construct that needs to be analyzed when understanding negative attitudes towards Muslims. To fully understand Islamophobia, it is important to examine the broader construct of racism so as to demonstrate Islamophobia as a subtype of racism. Islamophobia is growing with the rapid flow of global information, and the mass media is the main instrument in the dissemination of such information, giving rise to similar perceptions and actions against Islam. The relationship between Islamophobia and mass media is considered very close, so it can expand anti-Islamic attitudes.